1983
DOI: 10.1159/000234853
|View full text |Cite
|
Sign up to set email alerts
|

IgA Isotype Restriction in the Mucosal but Not in the Extramucosal Immune Response after Oral Immunizations with Cholera Toxin or Cholera B Subunit

Abstract: Intestinal mucosal as well as extramucosal antibody responses were studied in mice after peroral immunizations with cholera toxin or cholera B subunit. The immunizations with cholera toxin gave rise to a marked response with antitoxin-secreting cells (PFC) in Peyer’s patches (PP), mesenteric lymph nodes (MLN) and spleen showing isotype distribution of IgG > IgA > IgM and with PFC kinetics in MLN and spleen that suggested migration of cells from PP after peroral administration rather than cells stimulated in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…This isotype restriction is in accord with the 80-90% predomi nance of IgA-producing cells in the lamina propria [18] including specific antitoxin-containing cells [18,24], It also agrees with the isotype pattern for cholera antibodies in intestinal fluid [17]. Secretory IgA de rived from milk from mothers in cholera-endemic areas has been found to neutralize CT and afford pro tection to the breast-fed child [5,8].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This isotype restriction is in accord with the 80-90% predomi nance of IgA-producing cells in the lamina propria [18] including specific antitoxin-containing cells [18,24], It also agrees with the isotype pattern for cholera antibodies in intestinal fluid [17]. Secretory IgA de rived from milk from mothers in cholera-endemic areas has been found to neutralize CT and afford pro tection to the breast-fed child [5,8].…”
Section: Discussionsupporting
confidence: 75%
“…Cholera antitoxin antibodies were determined by means of an isotype-specific, enzyme-linked immunosorbent assay (ELISA) as previously described [17], Supernatants from the cultured cells were analyzed at an initial dilution of 1:3 and in serial triple dilutions. Antibody titers were defined as the interpolated dilutions of the samples which in 10 min gave rise to an absorbance of 0.2 above the background.…”
Section: Antibody Production In Cell Culturesmentioning
confidence: 99%
“…The presence of circulating anti-toxin-specific AFC in mice and humans after oral immunization with CT-B has been demonstrated using a similar ELISPOT technique by Lyke et al [13] but interestingly they were only able to demonstrate such cells using the ELISPOT technique after several days of in vitro culture. It might be that the use of the antibody amplification and the choice of solid media in the present study made the ELISPOT assay more sensitive, as we had no difficulty in demonstrating spontaneously secret- manifest a response but this was highly variable.…”
Section: Discussionmentioning
confidence: 97%
“…Lycke et al [13] found that after a second oral immunization with CT-B in mice, the peak circulating AFC response occurred after 4 to 8 days, which was in agreement with Kantele et al [18] who studied the AFC response after three immunizations of live Salmonella typi Ty2la given orally to humans who found a peak response at 8 days after the third immunization, and Forrest [17] who found a peak at 6 days after a third immunization of live Salmonella typhi Ty2la in humans. In contrast Czerkinsky et al [14] found a mean peak AFC response 10 to 12 days after oral immunization with killed S. rnutans in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that circulating IgG antibodies are also effectively stimulated by these approaches, thereby expanding the range of infections that can potentially be addressed by mucosal immunization (Lycke et al, 1983;Jackson et al, 1993). Cell-mediated immunity, including the generation of cytotoxic T lymphocytes (CTL), has been less frequently studied in this context; however, it is noteworthy that CTL with activity against HIV-infected cells can be induced by mucosal immunization with HIV peptides administered together with CT or LT(R192G) (Porgador et al, 1997;Belyakov et al, 2000).…”
Section: Applications and Significance With Respect To Oral Diseasementioning
confidence: 99%